The Comparative Ultrastructure of Fibrin Induced by Thrombin and by Staphylocoagulase - King, M. J. S; Morris, M. S; Tager, M (Thrombosis and Haemostasis, 1975)
Fibrin induced by the action of thrombin and by staphylocoagulase was studied by transmission electron microscopy.Periodic striations were consistently observed in the negatively stained preparations of both fibrins. When 4200 major periods in the thrombin fibrin system were measured the mean length was 228 Å. For 3666 major periods in the coagulase fibrin system the mean length was 223 Å. While the T test analysis of these values gave a value of 10, it is noteworthy that the differences are well within the scatter of periodicity reported in the literature for thrombin-induced fibrin.Gross inspection of the preparations indicated that the coagulase-induced fibrin had a knottier appearance and was accompanied by a greater amount of background debris than the thrombin-induced fibrin.